GENDER-BASED RESTORATIVE JUSTICE FOR VICTIMS OF VIOELENCE AGAINST WOMEN - Cahya Wulandari; Indung Wijayanto (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Positive law is less oriented towards the protection of victims, especially women. Restorative justice appears to protect and resolve problems with the interests of the victim-oriented. This article discuss the form of legal protection for victims of violence against women, gender-based and describe the form of restorative justice for victims of gender-based violence against women. Positive criminal law does not accommodate both the interests of the victim to determine the crime against him self and to restore his suffering. This is caused due to the dominance of retributive justice in the settlement mind set crime through the criminal law. The restorative justice allows for an active role in the completion of a crime victim who happens also allows the imposition of sanctions that are beneficial to the recovery of the suffering of the victims.Keywords: Victims; Violence against Women; Restorative Justice.